Effects of Feeding Increasing Amounts of Finishing Diet Blended with Nursery Diets on Growth Performance and Economics of Nursery Pigs - F. Wu; M. D. Tokach; J. C. Woodworth; C. W. Hastad; J. M. DeRouchey; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 1,260 pigs [PIC TR4 × (Fast LW × PIC L02); initial body weight (BW) 23.3 lb] were housed in two commercial research rooms and used in a 28-d study to determine the effects of blending increasing amounts of finishing feed into phase 3 nursery diets on pig growth performance. At weaning, pigs were placed into pens with 21 pigs per pen and 30 pens per room. Pigs were fed commercial nursery diets in a 5-phase feeding program with phases 1 and 2 fed before the start of the experiment. At the beginning of phase 3 (day 0), pens of pigs were blocked by pen weight and room. Within blocks, pens were allotted randomly to 1 of 4 treatments with 15 replications per treatment. Treatments consisted of a dose-titration of blending increasing amounts of late finishing feed (0, 2.75, 5.5, and 8.25 lb per pig, corresponding to 0, 3, 6, and 9 tons per 2,200-head barn, respectively) into a phase 3 nursery diet. Diet changes to the remaining phases were based on feed budgets. From day 0 to 14, average daily gain (ADG) was unaffected as finishing feed budget increased from 0 to 2.75 lb/pig but decreased thereafter (quadratic,P= 0.090). Average daily feed intake (ADFI) was unaffected, but feed-to-gain ratio (F/G) worsened (linear,P<0.001) as more finishing feed was blended into phase 3 nursery diet. From day 14 to 28, pigs previously fed increasing levels of late finishing feed had improved (linear,P<0.05) ADG and F/G, but unaffected ADFI. Overall (day 0 to 28), blending increasing amounts of finishing feed with phase 3 nursery diet decreased ADG (linear,P= 0.050) and tended to decrease (linear,P<0.07) ADFI and final BW. However, there was no evidence of any linear or quadratic effects of increasing finishing feed budgets on overall F/G. Feed cost, gain value, and feed cost per lb of gain decreased (linear,P<0.05) as finishing feed budget increased from 0 to 8.25 lb/pig. However, income over feed cost was not different among treatments. In conclusion, feeding increasing amounts of late finishing feed to phase 3 (28 lb) nursery pigs decreased overall ADG and ADFI, but did not affect income over feed cost.
Keywords: blending; finishing feed; growth; nursery feed; nursery pig